1977
DOI: 10.1073/pnas.74.6.2500
|View full text |Cite
|
Sign up to set email alerts
|

Binding of 25-hydroxycholesterol and cholesterol to different cytoplasmic proteins

Abstract: Studies were carried out to determine whether or not oxygenated derivatives of cholesterol (e.g., 25-hydroxycholesterol) that specifically suppress the activity of 3-hy-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…OSBP, the canonical mammalian ORP, was originally identified as a cytosolic protein that binds oxysterols (10,11), which are oxygenated derivatives of cholesterol and are important regulators of cholesterol metabolism (12). OSBP is representative of the larger ORP superfamily that is conserved from yeast to man (13)(14)(15)(16), and as discussed below, these proteins bind a variety of sterols.…”
Section: Osh Proteins: Non-vesicular Stps?mentioning
confidence: 99%
“…OSBP, the canonical mammalian ORP, was originally identified as a cytosolic protein that binds oxysterols (10,11), which are oxygenated derivatives of cholesterol and are important regulators of cholesterol metabolism (12). OSBP is representative of the larger ORP superfamily that is conserved from yeast to man (13)(14)(15)(16), and as discussed below, these proteins bind a variety of sterols.…”
Section: Osh Proteins: Non-vesicular Stps?mentioning
confidence: 99%
“…Recently, it has been demonstrated that 25-hydroxycholesterol inhibits the biosynthesis of HMG-CoA reductase . Although the mechanism by which 25-hydroxycholesterol produces its effects on HMG-CoA reductase biosynthesis is unknown, several binding studies (Kandutsch et al, 1977;Kandutsch and Thompson, 1980;Sinensky and Mueller, 1981) suggest that the initial site of action of this compound is a cytosolic protein.…”
mentioning
confidence: 99%
“…Different transport mechanisms for cholesterol and hydro¬ xylated sterols are likely. This is supported by the description of two cytosolic binding proteins in L-cells and foetal mouse liver cells (Kandutsch et al 1977 Binding of cholesterol to the cytochrome P-450 was reported to be rate-limiting in steroidogenesis (Mahaffee et al 1974;Williams-Smith et al 1976). …”
Section: Discussionmentioning
confidence: 80%